2014
DOI: 10.1002/pro.2598
|View full text |Cite
|
Sign up to set email alerts
|

Severing of a hydrogen bond disrupts amino acid networks in the catalytically active state of the alpha subunit of tryptophan synthase

Abstract: Conformational changes in the b2a2 and b6a6 loops in the alpha subunit of tryptophan synthase (aTS) are important for enzyme catalysis and coordinating substrate channeling with the beta subunit (bTS). It was previously shown that disrupting the hydrogen bond interactions between these loops through the T183V substitution on the b6a6 loop decreases catalytic efficiency and impairs substrate channeling. Results presented here also indicate that the T183V substitution decreases catalytic efficiency in Escherchia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Our analysis revealed that there are two networks of residues [colored orange and blue in Fig. (B)], and the residues involved in these networks change depending on what is bound to the protein . Intriguingly, Glu49, a residue directly involved in catalysis, belongs to different networks when comparing the apo resting state and when the enzyme is actively turning over substrate/products (i.e., the working state) .…”
Section: Enzymes As Amino Acid Interaction Networkmentioning
confidence: 95%
See 2 more Smart Citations
“…Our analysis revealed that there are two networks of residues [colored orange and blue in Fig. (B)], and the residues involved in these networks change depending on what is bound to the protein . Intriguingly, Glu49, a residue directly involved in catalysis, belongs to different networks when comparing the apo resting state and when the enzyme is actively turning over substrate/products (i.e., the working state) .…”
Section: Enzymes As Amino Acid Interaction Networkmentioning
confidence: 95%
“…These networks may also be important for how αTS communicates and coordinates channeling of its product indole into the active site of the beta subunit of tryptophan synthase (βTS). An amino acid substitution known to disrupt direct channeling of indole from the α‐ to β‐active sites also disrupts networks that might transmit structural dynamic information from the α‐active site to the α/β binding interface …”
Section: Enzymes As Amino Acid Interaction Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Other NMR studies on the enzyme tryptophan synthase have identified long-range allosteric pathways and have mechanistically investigated these pathways by mutations that disrupt critical interactions. 77,78 …”
Section: Nmr Spectroscopy In the Study Of Allosterymentioning
confidence: 99%
“…NMR chemical shift covariance analyses (CHESCA) and MD simulations are powerful tools to detect such amino acid networks when substrates or products are absent (resting state) and present (working state) in the active site [9597]. We investigated TRPS in its resting and working states to identify the correlation networks from a cluster of residues.…”
Section: Examples Of Modeling Enzymes and Substratesmentioning
confidence: 99%